Determining Digital Enabled Knowledge Sharing Effectivity Through SECI Model : Insight From Micro Insurance Marketing Synergy: Menentukan Efektivitas Berbagi Pengetahuan yang Didukung Teknologi Digital Melalui Model SECI: Wawasan dari Sinergi Pemasaran Asuransi Mikro - Abdillah, Sulthan Dzaki; Maesaroh, Syti Sarah; Prehanto, Adi (Indonesian Journal of Innovation Studies, 2025)
Background: Digital transformation has reshaped organizational knowledge practices, yet human-centred distribution still dominates microinsurance in Indonesia. Specific background: Despite structured knowledge-sharing mechanisms in the partnership between PT Asuransi X and PT Microfinance Y, unit-level performance varies widely. Knowledge gap: Existing studies seldom examine how knowledge conversion operates across inter-organizational settings, particularly where digital tools coexist with intensive field-based routines. Aim: This study analyzes how knowledge is converted through the Socialization, Externalization, Combination, and Internalization stages to explain variability in microinsurance outcomes. Results: Findings show that knowledge conversion is disrupted by passive middle leadership, informal gatekeeping, inadequate documentation, technological instability, fragmented data access, misaligned incentives, and inconsistent cross-institutional coordination. High-performing units show stronger mentoring cultures, proactive leadership, reliable hybrid routines, and more stable knowledge cycles. Novelty: This study extends the SECI model into a digital–human inter-organizational ecosystem, revealing stage-specific breakdowns that cannot be explained by digital infrastructure alone. Implications: Strengthening middle-layer leadership, formalizing mentoring, stabilizing digital systems, aligning incentives, and improving cross-organizational governance are crucial to sustaining consistent knowledge conversion in microinsurance networks. Highlights • Variability in microinsurance outcomes stems from stage-specific disruptions in the SECI cycle.• Middle-layer leadership and work culture determine whether knowledge flows or stalls across units.• Digital infrastructure alone is insufficient; consistent coordination and incentives are required for stable knowledge conversion. Keywords Knowledge Conversion, SECI Model, Digital Collaboration, Microinsurance Networks, Organizational Learning